Development of hyperbranched crosslinkers from bio-derived platform molecules for the synthesis of epoxidised soybean oil based thermosets. Issue 65 (6th November 2018) - Kamjornsupamitr, Trin; Hunt, Andrew J.; Supanchaiyamat, Nontipa
Abstract : Carboxyl-terminated hyperbranched crosslinkers have been synthesised by the facile esterification of glycerol with succinic anhydride. Gly-SA crosslinkers were used to cure epoxidised soybean oil to yield fully bio-derived thermosetting resins. Abstract : Bio-based carboxyl-terminated hyperbranched crosslinkers have been synthesised by the facile esterification reaction of glycerol with succinic anhydride (Gly-SA). The Gly-SA crosslinking molecules have a large number of terminal carboxyl groups, which can crosslink through the epoxide of epoxidised soybean oil (ESO), making a highly flexible transparent film with excellent oxidative resistance. The effect of different molecular weights of Gly-SA cured ESO on the thermal and mechanical properties of the resulting films was also investigated. This study demonstrated that an increase in the molecular weights of Gly-SA, led to a decrease in the curing rate of mixtures, whilst the glass transition temperature ( T g ) of Gly-SA cured ESO increased due to the incorporation of the bulky crosslinker. The use of a Gly-SA crosslinker prepared at 150 °C, resulted in a film (EGS150) with a tensile strength 13 times greater than of the control film, exhibited more than a 220% increase in elongation at break and the Young's modulus quadrupled compared to the value obtained for the control sample. It is noteworthy that the tensile strength and elongation at break improved with increasing Gly-SA chain length, suggesting the pre-polymerised crosslinkers contribute to the enhanced mechanical properties of the materials.